Identification of Core Gene Expression Signature and Key Pathways in Colorectal Cancer - Ding, Xiang; Duan, Houyu; Luo, Hesheng (Frontiers in Genetics, 2020)
Abstract Objective: Colorectal cancer (CRC) is among the most common and deadliest forms of cancer, but the signaling events and genes governing CRC pathology remain incompletely understood. As such, this study sought to identify novel biomarkers of CRC. Materials and methods: We obtained 20 clinical CRC samples from Renmin Hospital of Wuhan University. MAD2L1 expression changes in CRC were identified based upon integrated bioinformatics analyses of a GSE datasets. We then use qRT-PCR to validate that MAD2L1 expression was altered in CRC, and we used in vitro assays to explore its impact on the proliferation, cell cycle progression, and apoptotic death of CRC cells. Results: We indented 683 shared differentially expressed genes (DEGs) of which 420 and 263 were up- and downregulated, respectively. We then selected the top 20 genes from as integrated analytical approach as hub genes. These hub genes exhibited a pattern of positive correlation in their expression, and were markedly overexpressed in CRC tissue samples relative to healthy tissue controls. Of these genes, we found MAD2L1 expression in CRC tissues to be significantly increased, and when this gene was knocked down this led to suppression of the growth and cell cycle progression of CRC cells, leading to their apoptotic death. Conclusion: We identified MAD2L1 as a novel oncogene involved in CRC through its regulation of the growth and death of CRC cells, suggesting it may be a valuable diagnostic or therapeutic biomarker in those with CRC.